Changing microbial epidemiology in hematopoietic stem cell transplant recipients: increasing resistance over a 9‐year period. Issue 6 (9th October 2014) - Macesic, N.; Morrissey, C.O.; Cheng, A.C.; Spencer, A.; Peleg, A.Y.
Abstract Infections remain important contributors to mortality in hematopoietic stem cell transplantation (HSCT). Method We studied the evolving epidemiology and trends in susceptibility of bacterial and Candida isolates at an Australian HSCT center. A total of 528 HSCTs in 508 patients were performed from April 2001 to May 2010. A total of 605 isolates were eligible for study inclusion; 318 (53%) were gram‐positive, 268 (44%) were gram‐negative, and 19 (3%) were Candida species. Results The most common site for isolates was blood (380 isolates, 63%). Staphylococcus aureus was the most common gram‐positive organism (n = 107, 34%), but trends to increasing coagulase‐negative staphylococci (P = 0.002) and vancomycin‐resistant Enterococcus (P < 0.001) were observed. Escherichia coli was the most common gram‐negative isolate (n = 74, 28%). Fluoroquinolone resistance increased with widespread use of protocol fluoroquinolone prophylaxis (P = 0.001). Carbapenem resistance was found in 44% of Pseudomonas or Acinetobacter isolates. Bloodstream infection with a multidrug‐resistant organism (odds ratio 3.61, 95% confidence interval: 1.40–9.32, P = 0.008) was an independent predictor of mortality at 7 days after a positive blood culture. Conclusions Antimicrobial resistance is an increasing problem in this vulnerable patient population, and not only has an impact on choice of empiric therapy for febrile neutropenia but also on mortality.